Finance and Development, June 2004. (Finance and Development; Finance and Development ;, 2004)
This paper highlights that 10 new members joined the European Union on May 1, 2004, in the biggest enlargement of the community since its inception. However, the core economic concern is the weak growth performance of Europe-and particularly of the 12 countries at the epicenter of European integration that use the euro as their common currency-relative to the rest of the world and especially the United States. The paper highlights that underlying this concern are the problems of sagging long-term trends in the growth of productivity, and the use of labor resources.